Pengaruh Penerapan Model Pembelajaran Numbered Head Together untuk Meningkatkan Pemahaman Konsep Belajar Subtema Macam-Macam Sumber Energi Siswa Kelas IV Di SD Negeri 1 Selomanik Kabupaten Wonosobo - Gilang Satriya Utama (Peneliti.net, 2020)
The purpose of classroom action research is to determine whether the understanding of the concept of various energy sources for fourth grade students of Selomanik Elementary School 1 Semester I Academic Year 2020/2021 can be increased by using the Cooperative Learning Model Numbered Head Together (NHT). The research was carried out in two cycles, with stages namely planning, implementing and observing, and reflecting. The research variable consisted of one variable, namely the student's science learning outcomes. The data collection technique used non-test through observation and tests which consisted of multiple choice questions. The results showed that learning with the Numbered Head Together (NHT) cooperative learning model gave a better effect than the class with conventional learning models. In the experimental class, the NHT learning action increased by 18% with 100% completeness, while in the control class that applied the conventional learning model, there was an increase of only 9% from the average value in cycle I with a learning completeness value of 86.6%.